A Review Of Biodiesel Development In Indonesia: Current Status, Future Potential And Its Impact On The Environment - Lies Aisyah; Cahyo Setyo Wibowo (Scientific Contributions Oil and Gas, 2011)
Indonesian government issued National Energy Policy in 2006 that will reduce role of fossil fuels and increase role of renewable energy in 2025 as a target year. Bio-fuels are one of the renewable energy focuses in Indonesia. In 2009, biodiesel production capacity was 1.12 tons per year and expected to rise every year. Target of biodiesel usage increasesgradually from B-10 in 2006-2010, B-15 in 2011-2016 and B-20 in 2016-2025. The policy and its target are set by the government to diversification energy source, to boost economic growth (especially regional development and creation of employment) and to reduce greenhouse gas emissions. Currently the main feedstock of biodiesel in Indonesia is derived from palm oil. Some concerns arise related to palm oil biodiesel such as competition between food versus energy and environmental issue in particular replacing forest to oil palm plantations and biodiversity loss. Therefore, development of biodiesel feedstock from non-edible crops and can be grown in non-arable land are very important for future biodiesel development in order to eliminate competition with food and prevent deforestation and biodiversity loss.